Development of colorectal-targeted dietary supplement tablets containing natural purple rice bran oil as a colorectal chemopreventive - Busaban Sirithunyalug (2018)
© 2018 by the authors. Licensee MDPI, Basel, Switzerland. Colorectal cancer occurs due to various factors. The important risks are dietary lifestyle and inflammatory bowel diseases, such as Crohn’s disease and ulcerative colitis. It has been found that the inhibitory enzyme cyclooxygenase-2 (COX-2) in the colorectal region can potentially reduce the risk of colorectal cancer. The present study investigated rice bran oil from natural purple rice bran, which exhibits antioxidant and anti-inflammatory activity. This study aimed to evaluate the bioactive compound content of natural purple rice bran oil (NPRBO) derived from native Thai purple rice and the anti-inflammatory activity of NPRBO in colorectal cancer cells, and to develop a colorectal delivery platform in the form of film-coated tablets. NPRBO from the rice bran of five different Thai purple rice cultivars, namely Khao’ Gam Leum-Phua (KGLP), Khao’ Gam Boung (KGB), Khao’ Gam Thor (KGT), Khao’ Gam Pah E-Kaw (KGPEK), and Khao’ Niaw Dam (KND), were extracted using the supercritical carbon dioxide extraction technique. The amount of γ-oryzanol (ORY), tocotrienols, and tocopherols present in NPRBOs and the in vitro anti-inflammatory activity of NPRBO were investigated. The highest anti-inflammatory NPRBO was transformed into a dry and free-flowing powder by liquisolid techniques. Then, it was compressed into core tablets and coated with Eudragit®L100 and Eudragit® NE30D. The in vitro release study of the film-coated NPRBO tablets was performed in three-phase simulated gastrointestinal media. The cultivar KGLP was superior to the other samples in terms of the ORY, tocotrienol and tocopherol contents and anti-inflammatory activity. Aerosil® was the most suitable absorbent for transforming NPRBO into a free-flowing powder and was used to prepare the NPRBO core tablets. The in vitro KGLP-NPRBO film-coated tablet release profile showed that no ORY was released at gastric pH while 85% of ORY was released at pH 7.4 after 6 h; this would be expected to occur in the colorectal area. Therefore, this study demonstrates the potential of KGLP-NPRBO to prevent colorectal cancer via a specific colorectal dietary supplement delivery system.